Developing an Ecoliteracy E-Module through the ADDIE Model to Foster Sustainable Development (SDGs) in Elementary Schools - Puspitasari, Ai Nina Karlina; Soemantri, Mubarok (International Conference on Elementary Education, 2025)
This research is motivated by the importance of ecoliteracy education in elementary schools to instill sustainable values. Integrating the Sustainable Development Goals (SDGs) into learning is a strategic step to foster environmental awareness through a digital approach. This study aims to develop an e-module on ecoliteracy integrated with the SDGs for elementary school students, using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). This research method uses a research and development (R&D) design with a mixed methods approach. The subjects were 50 students, divided into two groups: an experimental group and a control group (25 students each). Quantitative data were collected through pre-tests and post-tests, while qualitative data were obtained through interviews and observations. Findings and analysis showed that the experimental group achieved a post-test score of 85% with an N-gain of 0.6 (moderate), while the control group achieved 70% with an N-gain of 0.2 (low). These data indicate an increase in students' understanding of the ecoliteracy concept after the e-module. In conclusion, the ADDIE-based ecoliteracy e-module has proven effective in strengthening environmental awareness and supporting sustainability-focused education in elementary schools.